Insights on the Permian tuff beds from the Saint-Affrique Basin (Massif Central, France): an integrated geochemical and geochronological study - Poujol, Marc; Mercuzot, Mathilde; Lopez, Michel; Bourquin, Sylvie; Bruguier, Olivier; Hallot, Erwan; Beccaletto, Laurent (Comptes Rendus. Géoscience)
The Permian marks the transition between the end of the accretion of the supercontinent Pangea and the beginning of its dislocation. In the Eastern Pangea intertropical domain (i.e. the present-day Western Europe), the late-Paleozoic (i.e. uppermost Carboniferous–Permian) history remains poorly constrained due to the lack of precise radiometric data. This is particularly true for Permian basins from the southern part of the French Massif Central, making it difficult to determine correlations between basins and therefore robust timings and constraints on the environmental and climate events described in these basins, and to compare them with the larger-scale settings. This article focuses on the Saint-Affrique Basin, via an integrated petrological, geochemical and geochronological study of eight of the volcanic-ash levels interbedded in the sedimentary succession. It highlights the existence of two different groups of felsic volcaniclastic rocks. The first group, located at the base of the basin and attributed to the Stephanian continental stage, is related to a late-orogenic volcanic setting and corresponds to calc-alkaline trachy-andesitic tuffites that could not be dated due to the lack of volcanic zircon. The second group, located towards the top of the succession, is composed of calc-alkaline dacitic ash beds and tuffites yielding Kungurian ages, i.e. late early Permian (Cisuralian, $283.5± 0.6$ to $273.01± 0.14~Ma$), and are attributed to a post-orogenic deposition setting. These ages show that the sedimentary filling of the basin is younger than hitherto expected (i.e. Artinskian, $290.1± 0.26$ to $283.5± 0.6~Ma$). The elemental geochemistry, the presence of inherited detrital zircons and the Hf signatures of the volcanic ones indicate the involvement of an old (Proterozoic and older) basement in the magma genesis; this crustal contribution becomes more prominent towards the top of the sedimentary succession.